Just Between Us : An Ethnography of Male Identity and Intimacy in Rural Communities of Northern Mexico - Núñez Noriega, Guillermo (Book collections on Project MUSE., 2014)
"Just Between Us, set in the context of Mexico's cultural codes, challenges norms in thinking about men's identities, their pleasures, and their sense of belonging. Author Guillermo Núñez Noriega offers a groundbreaking study that contests patriarchal concepts limiting male relationships and masculinity"--Provided by publisher.